Odpowiedzi

Najlepsza Odpowiedź!
2010-03-23T20:31:24+01:00
A .
0,2x + 0,3 =-0,5
0,2x = -0,5 - 0,3
0,2x = -0,8/:0,2
x = -4

b .
0,4 + 0,25x = -2
0,25x = -2 - 0,4
0,25x = -2,4/:0,25
x = -9,6

c .
2,1 - 0,3x = 0,4x
-0,4x - 0,3x = -2,1
-0,7x = -2,1/:(-0,7)
x = 3

d .
-1,5x - 3 = 0,2x + 6
-1,5x - 0,2x = 6 + 3
-1,7x = 9 /:(-1,7)
x = -5,29
2010-03-23T20:33:19+01:00
A)
0,2x+0,3 = -0,5
0,2x = -0,5-0,3
0,2x = -0,8 |:0,2
x = -4

b)
0,4+0,25x = -2
0,25x = -2-0,4
0,25x = -2,4 |:0,25
x = -9,6

c)
2,1-0,3x = 0,4x
2,1 = 0,4x+0,3x
0,7x = 2,1 |:0,7
x = 3

d)
-1,5x-3 = 0,2x+6
-1,5x-0,2x = 6+3
-1,7x = 9 |:-1,7
x = 5i5/17